2019
DOI: 10.1103/physrevd.100.084037
|View full text |Cite
|
Sign up to set email alerts
|

Static compact objects in Einstein-Cartan theory

Abstract: We generalize the Tolman-Oppenheimer-Volkoff equations for space-times endowed with a Weyssenhoff like torsion field in the Einstein-Cartan theory. The new set of structure equations clearly show how the presence of torsion affects the geometry of the space-time. We obtain new exact solutions for compact objects with non-null intrinsic spin surrounded by vacuum, explore their properties and discuss how these solutions should be smoothly matched to an exterior space-time.We study how the intrinsic spin of matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…With Eq. 159 in [43], a solution was presented for inner stars with junction to the outside leading to B(r) = (a + br 2 ) 2 which would mean with our solution…”
Section: Comparison With Known Solutionsmentioning
confidence: 73%
See 3 more Smart Citations
“…With Eq. 159 in [43], a solution was presented for inner stars with junction to the outside leading to B(r) = (a + br 2 ) 2 which would mean with our solution…”
Section: Comparison With Known Solutionsmentioning
confidence: 73%
“…Further treatments can be performed numerically dependent on the given momentum and density profile via the equation of state. Exact solutions for the inner region of compact objects are discussed in [41,43,67], for rotating stars in [42] and possible upper limits of masses of stars in [44].…”
Section: B Internal Schwarzschild Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in [7,8] it was shown that the generating theorems proposed by Boonserm et al in [20,21] can be easily formulated and extended to more complex cases. The 1+1+2 TOV equations have also been used to uncover new features of relativistic stellar objects in Einstein-Cartan gravity in [22].…”
Section: Introductionmentioning
confidence: 99%